3D sub-diffraction imaging in a conventional confocal configuration by exploiting super-linear emitters - Denitza Denkova (Nature Portfolio, 2019)
Super-resolution microscopy is a valuable tool in bioimaging, but often requires complex systems or post-processing. Here, the authors present super-linear excitation-emission (SEE) microscopy, which overcomes these limitations by taking advantage of markers with super-linear dependence between emission and excitation power.